Repression by the Arabidopsis TOPLESS corepressor requires association with the core mediator complex - Leydon, Alexander R; Wang, Wei; Gala, Hardik P; Gilmour, Sabrina; Juarez-Solis, Samuel; Zahler, Mollye L; Zemke, Joseph E; Zheng, Ning; Nemhauser, Jennifer L (eLife, 2021)
The plant corepressor TOPLESS (TPL) is recruited to a large number of loci that are selectively induced in response to developmental or environmental cues, yet the mechanisms by which it inhibits expression in the absence of these stimuli are poorly understood. Previously, we had used the N-terminus of Arabidopsis thaliana TPL to enable repression of a synthetic auxin response circuit in Saccharomyces cerevisiae (yeast). Here, we leveraged the yeast system to interrogate the relationship between TPL structure and function, specifically scanning for repression domains. We identified a potent repression domain in Helix 8 located within the CRA domain, which directly interacted with the Mediator middle module subunits Med21 and Med10. Interactions between TPL and Mediator were required to fully repress transcription in both yeast and plants. In contrast, we found that multimer formation, a conserved feature of many corepressors, had minimal influence on the repression strength of TPL.